Contextualized Montessori teacher training: A learning impact evaluation - Dinda Adiesty Kusumawardani; Rusman Rusman (Curricula: Journal of Curriculum Development, 2025)
Early childhood education plays a strategic role in shaping the holistic development of children. However, the implementation of the Montessori approach in Indonesia still faces several challenges, including limited teacher training and a lack of cultural contextual alignment. This study aims to evaluate the impact of a contextualized Montessori teacher training program, which includes limited teacher training and inadequate knowledge improvement among early childhood educators. The research employed a quasi-experimental method with a one-group pretest-posttest design, without a control group. A total of 20 teachers from KB TKIT AsySyaffa 1 Magelang participated in a three-month training program. The impact of the training was measured using Kirkpatrick's Level 2 (learning) evaluation model, with a validated 17-item test instrument. Tests for normality and homogeneity confirmed that the data met the assumptions for parametric analysis. The paired sample t-test revealed a significant difference between pretest and posttest scores, indicating an increase in teachers’ knowledge after the training. These findings affirm that contextualized Montessori training effectively enhances teacher understanding and has the potential to strengthen the implementation of the Montessori approach in Indonesia’s early childhood education system.   Abstrak Pendidikan anak usia dini memegang peran strategis dalam membentuk fondasi perkembangan anak secara holistik. Di sisi lain, penerapan pendekatan Montessori di Indonesia masih menghadapi sejumlah tantangan, seperti keterbatasan pelatihan guru dan kesesuaian dengan konteks budaya lokal. Penelitian ini dilakukan untuk mengukur efektivitas dampak pelatihan guru Montessori yang dikontekstualisasikan terhadap peningkatan pengetahuan guru PAUD sebagai bagian dari evaluasi level 2 model Kirkpatrick. Penelitian menggunakan metode kuasi-eksperimen dengan desain one-group pretest-posttest tanpa kelompok kontrol. Sebanyak 20 guru dari KB TKIT AsySyaffa 1 Magelang menjadi peserta pelatihan yang berlangsung selama tiga bulan. Pengukuran dampak pelatihan dilakukan menggunakan model evaluasi Kirkpatrick level 2 (learning), dengan instrumen tes berisi 17 butir soal validasi. Hasil uji normalitas dan homogenitas menunjukkan data memenuhi syarat analisis parametrik. Uji paired sample t-test menunjukkan adanya perbedaan signifikan antara skor pretest dan posttest, yang mengindikasikan peningkatan pengetahuan guru setelah pelatihan. Temuan ini menegaskan bahwa pelatihan Montessori berbasis kontekstual efektif dalam meningkatkan pemahaman guru dan berpotensi memperkuat implementasi pendekatan Montessori dalam sistem pendidikan anak usia dini di Indonesia. Kata Kunci: evaluasi Kirkpatrick; Montessori; PAUD; pelatihan guru; pembelajaran kontekstual